The effect of gadget use on emotional intelligence, social behavior, and religious behavior of generation z students in muhammadiyah 2 senior high school of yogyakarta - safaroh fananda; Nawari Ismail; Siti Bahiroh (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study is aimed to (1) describe the effect of gadget use on emotional intelligence, (2) describe the effect of gadget use on social behavior, (3) describe the effect of gadget use on students' religious behavior. Quantitative approach was used in this research. The research subjects were collected using the cluster proportional random sampling technique. Data of this study were collected by using techniques using questionnaires, interviews, and documentation. The data were analyzed with a simple linear regression test. This study showed that (1) there is a significant effect of gadget use on emotional intelligence, (2) there is a significant effect of gadget use on social behavior, (3) there is a significant effect of gadget use on students' religious behavior.